A Review on Development Prospect of CZTS Based Thin Film Solar Cells. (26th May 2014) - Song, Xiangbo; Ji, Xu; Li, Ming; Lin, Weidong; Luo, Xi; Zhang, Hua
Abstract : Cu2 ZnSnS4 is considered as the ideal absorption layer material in next generation thin film solar cells due to the abundant component elements in the crust being nontoxic and environmentally friendly. This paper summerized the development situation of Cu2 ZnSnS4 thin film solar cells and the manufacturing technologies, as well as problems in the manufacturing process. The difficulties for the raw material's preparation, the manufacturing process, and the manufacturing equipment were illustrated and discussed. At last, the development prospect of Cu2 ZnSnS4 thin film solar cells was commented.